Place making in Non-places: Migrant Graffiti in Rural Highway Box Culverts - Soto, Gabriella (Journal of Contemporary Archaeology, 2017)
This paper describes particular material phenomenon resulting from the mass movement of undocumented migrants across the border from Mexico into Arizona, with a particular focus on migrant graffiti panels found hidden beneath rural highways. I use Marc Auge’s (2006) conceptualization of ‘non-places’ as a framework for seeking to understand the meaning behind the material impact of clandestine and undocumented migration alongside and underneath the otherwise sterile spaces of official mass transit. This paper interrogates the weight and meaning behind the actions of so-called ‘illegitimate’ or ‘illegal’ migrant travelers as they build history and create a sense of place in the non-places of the borderlands, all while evading the United States border security.